Neuromuscular onset succession of high level gymnasts during dynamic leg acceleration phases on high bar - von Laßberg, C.; Rapp, W.; Mohler, B.; Krug, J. (Journal of Electromyography and Kinesiology, 2013)
In several athletic disciplines there is evidence that for generating the most effective acceleration of a specific body part the transfer of momentum should run in a "whip-like" consecutive succession of body parts towards the segment which shall be accelerated most effectively (e.g. the arm in throwing disciplines). This study investigated the question how this relates to the succession of neuromuscular activation to induce such "whip like" leg acceleration in sports like gymnastics with changed conditions concerning the body position and momentary rotational axis of movements (e.g. performing giant swings on high bar). The study demonstrates that during different long hang elements, performed by 12 high level gymnasts, the succession of the neuromuscular activation runs primarily from the bar (punctum fixum) towards the legs (punctum mobile). This demonstrates that the frequently used teaching instruction, first to accelerate the legs for a successful realization of such movements, according to a high level kinematic output, is contradictory to the neuromuscular input patterns, being used in high level athletes, realizing these skills with high efficiency.